Alpha 1 Antitrypsin Deficiency Pathophysiology, Symptoms, Diagnosis, Treatment - Kościelecki , Kamil; Kalisz, Agnieszka; Okońska, Aleksandra; Kozakiewicz, Julia; Skorulska, Iwona; Długozima, Patrycja; Głowacka, Aleksandra; Grywińska, Weronika Barbara; Grzeszczuk, Paulina; Mączewska, Klaudia (Quality in Sport, 2025)
Introduction: This review paper aims to emphasize how Alpha-1-antitrypsin deficiency is how can lead to serious disease states, indicating the pathophysiology, symptoms, diagnostic possibilities, therapeutic methods and proving that early diagnostics for this deficiency can protect the patient from its serious consequences Materials and methods: A review of chosen literature in the PubMed database was conducted, using the following keywords: „Alpha-1-antitrypsin deficiency”, „Alpha-1-antitrypsin” Summary: Alpha-1-antitrypsin deficiency is a relatively common condition that is often overlooked in diagnostic evaluations. It can lead to serious health complications, substantially reduce quality of life, and even shorten a patient's lifespan. Early diagnosis is essential because it allows for the adoption of healthier lifestyle habits and more consistent health monitoring, which can help mitigate the condition’s long-term consequences. Conclusions: Symptoms of alpha-1 antitrypsin deficiency are quite prevalent and can affect individuals across all age groups—from infants and children to adults and the elderly. This deficiency may lead to serious complications, including COPD, emphysema, asthma, liver cirrhosis, hepatocellular carcinoma (HCC). A deep understanding of its pathophysiology has enabled the development of improved diagnostic techniques and novel treatment strategies. For instance, in young adults with COPD and children exhibiting signs of liver disease, it is advisable to measure alpha-1 antitrypsin levels or perform genotyping. In cases where a significant deficiency is detected, initiating replacement therapy and closely monitoring the patient's health is crucial.